Esophagogastric junction cancer successfully treated by laparoscopic proximal gastrectomy and lower esophagectomy with intrathoracic double‐flap technique: A case report. Issue 2 (30th August 2017) - Hosoda, Kei; Yamashita, Keishi; Moriya, Hiromitsu; Washio, Marie; Mieno, Hiroaki; Ema, Akira; Watanabe, Masahiko
Abstract: A 66‐year‐old man was referred to our hospital for treatment of esophagogastric junction cancer. He was diagnosed as cT2N0M0, and the esophageal invasion was found to be 1 cm from the esophagogastric junction. He underwent laparoscopy‐assisted proximal gastrectomy and lower esophagectomy with esophagogastrostomy using the intrathoracic double‐flap technique through the transhiatal approach. The operative time was 662 min (suturing time was 198 min), and blood loss was 200 mL. The operative time was much longer for this procedure than for esophagogastrostomy with the conventional (intra‐abdominal) double‐flap technique. The postoperative course was uneventful. No abnormal gastroesophageal reflux, esophageal motility, or lower esophageal sphincter (LES) pressure was demonstrated 3 months after the operation. Laparoscopic proximal gastrectomy and lower esophagectomy with esophagogastrostomy using the double‐flap technique through the transhiatal approach is safe and feasible. It may be recommended for patients with esophagogastric junction cancer with esophageal invasion of about 1 cm.